Insight into microstructure-sensitive elastic strain concentrations from integrated computational modeling and digital image correlation. (February 2021) - Latypov, Marat I.; Stinville, Jean-Charles; Mayeur, Jason R.; Hestroffer, Jonathan M.; Pollock, Tresa M.; Beyerlein, Irene J.
Graphical abstract: Abstract: The microstructural origins of highly localized elastic strain concentrations in polycrystalline microstructures under monotonic loading are studied using grain-scale, in situ digital image correlation and crystal plasticity finite element method. It is shown that the locations of exceptionally high elastic strain concentrations in the microstructure depend on particular crystallographic and morphological orientations of grains and less so on crystalline details of their local neighborhood. Based on these results, we discuss how topological and crystallographic features of annealing twin boundaries can increase the likelihood of slip band initiation throughout the microstructure of polycrystalline Ni-base superalloys.